Brief exposure to (-) THC affects zebrafish embryonic locomotion with effects that persist into the next generation - Md Ruhul Amin; Lakhan Khara; Joshua Szaszkiewicz; Andrew M. Kim; Trevor J. Hamilton; Declan W. Ali (Scientific Reports)
Abstract Cannabis is one of the most widely used drugs, and yet an understanding of its impact on the human brain and body is inconclusive. Medicinal and recreational use of cannabis has increased in the last decade with a concomitant increase in use by pregnant women. The major psychoactive compound in cannabis, Δ9-tetrahydrocannabinol (THC), exists in different isomers, with the (-) trans isomer most common. Prenatal exposure to THC can alter neural and behavioral development, but it is unknown how exposure to (-) trans-THC ((-)THC) during very early stages of development impacts fetal growth and movement, and whether effects persist to adulthood, or into the next generation. Here we exposed zebrafish (Danio rerio) to a single exposure of (-)THC (0.001 mg/L (3.2 nM) to 20 mg/L (63.6 µM), for 5 h) during gastrulation (5.25 hpf to 10.75 hpf) when key neurons involved in locomotion such as the primary motor neurons and Mauthner cell first appear. We then examined the impact on embryo morphology and locomotion, adult behavior, and locomotion in the next (F1) generation. Embryos treated with (-)THC experienced changes in morphology, were shorter in length and experienced altered hatching and survival. Spontaneous coiling of 1 dpf embryos was reduced, swimming after touch-evoked responses was reduced and basal swimming in 5 dpf larvae was also reduced. Adult zebrafish tested in the open field test and novel object approach test demonstrated no differences in locomotion, anxiety-like behavior, nor boldness, compared to controls. The (-)THC F1 generation embryos at 1 dpf showed reduced coiling activity, while swimming after touch-evoked responses was reduced in 2 dpf animals but basal swimming at 5 dpf remained similar to controls. Taken together, exposure to (-)THC only once for 5 h during gastrulation has a significant impact on locomotion in embryos and larvae, a minimal impact on adult behavior, and effects that persist into the next generation.